1973
DOI: 10.1210/jcem-37-2-341
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four-Hour Cycle of a Melatonin-Like Substance in the Plasma of Human Males

Abstract: Plasma samples obtained during darkness from 5 male volunteers contained a substance with melanin aggregating and chromatographic properties similar to those of melatonin. Peak levels were apparently inversely related to pineal calcification and/or age. Neither this substance nor an inhibitor against its biologic activity was detected in daytime samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
32
0
1

Year Published

1974
1974
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(38 citation statements)
references
References 9 publications
(10 reference statements)
5
32
0
1
Order By: Relevance
“…This phenomenon may be due to increased pineal synthesis and secretion of melatonin following blinding. Blinding or constant darkness results in a large increase in the activity of the melatonin-synthesizing enzymes in the rat pineal (28,29), and recently it was shown (30) that the concentration of a melatonin-like substance increases in the plasma of humans kept in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be due to increased pineal synthesis and secretion of melatonin following blinding. Blinding or constant darkness results in a large increase in the activity of the melatonin-synthesizing enzymes in the rat pineal (28,29), and recently it was shown (30) that the concentration of a melatonin-like substance increases in the plasma of humans kept in darkness.…”
Section: Discussionmentioning
confidence: 99%
“…The serum serotonin of the rat increases at the beginning of the dark phase, but also at the end of the light phase Ralph, 1975). Melatonin secretion has also been observed to increase at the beginning of darkness in ewes (Rollag and Niswender, 1976) and in man (Pelham et al,1973 …”
mentioning
confidence: 96%
“…In the rat, pinealectomy abolishes the diurnal rhythm in prolactin secretion (Ronnekleiv et al, 1973) as well as blocking the increase in prolactin observed in rats kept in continuous darkness (Relkin, 1972) Ralph, 1975). Melatonin secretion has also been observed to increase at the beginning of darkness in ewes (Rollag and Niswender, 1976) and in man (Pelham et al,1973 Acknowledgments. …”
mentioning
confidence: 98%
“…Fluctuations in blood melatonin levels in response to a light-dark transition have been demonstrated in the sheep (Rollag and Niswender 1976), the rat (Ozaki et al 1976) and in man (Pelham et al 1973). The present work has established that in M. leonina blood melatonin levels exhibit a circadian variation, which is much more marked in winter (approximately 16 h of darkness) than in summer (approximately 5 h of darkness).…”
Section: Discussionmentioning
confidence: 99%